Effects of defaunation of large seed dispersers, habitat loss and fragmentation on the population expansion of a tropical palm - Fernandes, Patrick Faria; de Avelar São-Pedro, Vinícius; de Lima Souza, Breno [UNESP]; Moreira-Silva, Camila [UNESP]; de Cássia Quitete Portela, Rita; Mendes, Eduardo Teles Barbosa; de Oliveira Scarascia, Pietro; da Silva Carvalho, Carolina (Springer Nature, 2025)
Content: Habitat loss and fragmentation are two processes resulting from land-use changes that significantly affect biodiversity worldwide. These two processes alongside illegal hunting are the main causes of the reduction in fauna diversity, richness, and biomass, which together characterize defaunation. Large animal species are the most affected by this process, compromising ecosystem services such as seed dispersal. Objectives: We evaluated the isolated and combined effects of habitat loss, fragmentation and the nonrandom defaunation of large seed dispersers on the population expansions of the tropical palm Euterpe edulis. Methods: We modeled the spatial dynamics of the species via RangeShiftR in landscapes with different degrees of habitat percentage and fragmentation, simulating two distinct scenarios: nondefaunated, with a complete assembly of avian seed dispersers, and defaunated, with an impoverished assembly of large avian frugivores. Then, we developed linear regression models using the total abundance and density at the end of a 100-year simulation as response variable, and we selected the best model based on the Akaike information criterion. Results: Habitat loss, fragmentation, and defaunation negatively affect the abundance and density of E. edulis. Furthermore, the interaction effect between defaunation and habitat percentage was significant, indicating that in nondefaunated scenarios, the abundance and density of E. edulis increase substantially. Additionally, habitat loss has a greater negative effect on population expansion than fragmentation, which has a lower predictive power. Conclusion: These results help address the effects of habitat loss, fragmentation and defaunation on the population expansion of E. edulis. Our models contribute to the strategic planning of actions aimed at the conservation of E. edulis, highlighting habitat loss as a central point in allocating efforts for the protection of this species, as well as the importance of considering fauna data in estimates of the population expansion capacity of plant species.
Keywords: Arecaceae; Atlantic forest; Euterpe edulis; Plant conservation; Population modeling; RangeShiftR